2-methyl-1H-indole-3-carbaldehyde 2-thienoylhydrazone - Ali, Hapipah Mohd; Ng, S.W.; Xie, M.J.; Najwa, M.I. (International Union of Crystallography, 2006)
In the title compound, C15H13N3OS, the amide H atom interacts with the amide O atom of an adjacent molecule [N center dot center dot center dot O = 3.027 (4) angstrom] to form a zigzag chain that runs along the c axis of the monoclinic unit cell.